Association and interaction analysis of NLRP3 gene polymorphisms with hypertension risk: a case–control study in China - Wanning Xia; Mingming Qi; Yupeng Liu; Jing Mi; Jian Song; Xuesen Wu (BMC Cardiovascular Disorders)
Abstract Background The NLRP3 inflammasome, a pivotal mechanism regulating inflammatory responses and featuring the pyrin domain containing 3 (NLRP3) within the NOD-like receptor family, is widely recognized as a central pathogenic factor in cardiovascular diseases. The present study endeavors to delve into the correlation and potential interplay between the rs10754558 polymorphism of NLRP3 and the predisposition to hypertension among the Chinese adult population. Methods All the participants who came from a community in Bengbu, China were investigated by being interviewed with a questionnaire. Overall, 354 paired case–control participants were analyzed. Genomic DNA was extracted from 5ml venous blood using the Tiangen DNA extraction kit. The rs10754558 polymorphism of the NLRP3 gene was genotyped by TaqMan allelic discrimination real-time PCR.The association between the rs10754558 polymorphism and hypertension risk was investigated by a logistic regression analysis. Furthermore, an additive interaction analysis was conducted using related indicators, including the relative excess risk due to interaction (RERI), attributable proportion due to interaction (AP), and synergy index (SI). Results Participants carrying the GG genotype were more likely to develop hypertension than participants carrying the CC genotype (adjusted odds ratio [OR]: 2.16, 95% confidence interval [CI]: 1.33–3.52). A significant additive interaction between the NLRP3 polymorphism and obesity status concerning the risk of hypertension was observed, as estimated by all indicators: RERI (1.12, 95% CI: 0.70–1.5), AP (0.34, 95% CI: 0.14–0.53), and SI (1.92, 95% CI: 1.03–3.59). The values of RERI (1.74, 95% CI: 0.37–3.11), AP (0.46, 95% CI: 0.21–0.70), and SI (2.62, 95% CI: 1.18–5.83) showed that a significant interaction between the rs10754558 polymorphism and a family history of hypertension. Conclusions Our findings indicate a significant association between the NLRP3 rs10754558 polymorphism and the risk of hypertension in Chinese adults. Moreover, a notable additive interaction emerges between NLRP3 polymorphisms and obesity status, further amplifying the risk of hypertension.